The African Charter on the Rights and Welfare of the Child: A socio-legal perspective - Thoko Kaime (Pretoria University Law Press (PULP), 2009)
The African Charter on the Rights and Welfare of the Child: A socio-legal perspective by Thoko Kaime 2009 ISBN: 978-0-9814420-4-4 Pages: xii 247 Print version: Available Electronic version: Free PDF available